ISG15 deficiency features a complex cellular phenotype that responds to treatment with itaconate and derivatives. Issue 7 (17th July 2022) - Waqas, Syed Fakhar‐ul‐Hassnain; Sohail, Aaqib; Nguyen, Ariane Hai Ha; Usman, Abdulai; Ludwig, Tobias; Wegner, Andre; Malik, Muhammad Nasir Hayat; Schuchardt, Sven; Geffers, Robert; Winterhoff, Moritz; Merkert, Sylvia; Martin, Ulrich; et al.
Abstract: Background: Congenital ISG15 deficiency is a rare autoinflammatory disorder that is driven by chronically elevated systemic interferon levels and predominantly affects central nervous system and skin. Methods and results: We have developed induced pluripotent stem cell‐derived macrophages and endothelial cells as a model to study the cellular phenotype of ISG15 deficiency and identify novel treatments. ISG15 –/– macrophages exhibited the expected hyperinflammatory responses, but normal phagocytic function. In addition, they displayed a multifaceted pathological phenotype featuring increased apoptosis/pyroptosis, oxidative stress, glycolysis, and acylcarnitine levels, but decreased glutamine uptake, BCAT1 expression, branched chain amino acid catabolism, oxidative phosphorylation, β‐oxidation, and NAD(P)H‐dependent oxidoreductase activity. Furthermore, expression of genes involved in mitochondrial biogenesis and respiratory chain complexes II–V was diminished in ISG15 –/– cells. Defective mitochondrial respiration was restored by transduction with wild‐type ISG15, but only partially by a conjugation‐deficient variant, suggesting that some ISG15 functions in mitochondrial respiration require ISGylation to cellular targets. Treatment with itaconate, dimethyl‐itaconate, 4‐octyl‐itaconate, and the JAK1/2 inhibitor ruxolitinib ameliorated increased inflammation, propensity for cell death, and oxidative stress. Furthermore, the treatments greatly improved mitochondria‐related gene expression, BCAT1 levels, redox balance, and intracellular and extracellular ATP levels. However, efficacy differed among the compounds according to read‐out and cell type, suggesting that their effects on cellular targets are not identical. Indeed, only itaconates increased expression of anti‐oxidant genes NFE2L2, HMOX1, and GPX7, and dimethyl‐itaconate improved redox balance the most. Even though itaconate treatments normalized the elevated expression of interferon‐stimulated genes, ISG15 –/– macrophages maintained their reduced susceptibility to influenza virus infection. Conclusions: These findings expand the cellular phenotype of human ISG15 deficiency and reveal the importance of ISG15 for regulating oxidative stress, branched chain amino acid metabolism, and mitochondrial function in humans. The results validate ruxolitinib as treatment for ISG15 deficiency and suggest itaconate‐based medications as additional therapeutics for this rare disorder. Abstract : ISG15 deficiency triggers hyperinflammation, apoptosis/pyroptosis, and oxidative stress, while reducing mitochondrial respiration and biogenesis, branched chain amino acid catabolism, and viral infectivity. Itaconates and the JAK1/2 inhibitor ruxolitinib ameliorate this dysregulated phenotype, identifying them as potential therapeutic options for this rare disorder.